EFFECT OF HUMAN MILK ON DEVELOPMENT OF RETINOPATHY OF PREMATURITY - Fatima, Bushra; Chisti, Akmal Laeeq; Sadiq, Muhammad Ali; Fatima, Tehreem; Karamat, Muhammad Irfan (Pakistan Armed Forces Medical Journal, 2019)
Objective: To determine the protective effect of human milk on development of retinopathy of prematurity (ROP) in preterm babies. Study Design: Observational study. Place and Duration of Study: King Edward Medical University Lahore, Department of pediatrics over a period of 11 months, from Feb 2016 to Dec 2016. Material and Methods: A total 142 preterm babies with birth weight <2.5kg and gestation age <37 weeks were included by non-probability convenient sampling. Neonates were assessed and grouped according to the type of feeding. Eye examination was performed minimally at 4 weeks of life and then serially by trained consultant in the Department of Ophthalmology. Data were analyzed through SPSS 20.0 and Chi square test was applied. Results: Mean age at enrollment was 11.22 ± 16.48 days. Mean gestational age was 33.1 ± 13.06 weeks and mean birth weight recorded was 1.7 ± 0.43 kilograms. Among the study cases, 84 (59.2%) babies were on human milk and 58 (40.8%) were taking formula milk. Mean duration of oxygen therapy was 3.7 ± 3.77 days. Changes compatible with ROP was found in 9 (6.3%) cases. Among human milk fed babies, three babies (3.57%) developed ROP and in formula fed group, 6 (10.3%) babies developed changes of ROP. Thus, the risk of developing ROP was higher in formula milk fed babies as compared to human milk. However protective effect was not statistically significant as shown by value of Chi-square test: 2.65 (p-value=0.103). Conclusion: Though human milk was protective for the development of ROP but result was not statistically significant.